Long-term efficacy and cost-effectiveness of blended cognitive behavior therapy for high fear of recurrence in breast, prostate and colorectal Cancer survivors: follow-up of the SWORD randomized controlled trial - Burm, Rens (BMC Cancer, 2019)
BACKGROUND: Blended cognitive behaviour therapy (bCBT) is an effective treatment for fear of cancer recurrence (FCR) in curatively-treated breast, colorectal and prostate cancer survivors with high FCR. However, long-term outcomes are unknown. This study investigated the long-term efficacy and cost-effectiveness of bCBT compared with care as usual (CAU). METHODS: Eighty-eight cancer survivors with high FCR (Cancer Worry Scale ≥14) were randomly assigned to bCBT (n = 45) or CAU (n = 43). Data were collected at baseline and at three, nine and fifteen months from baseline and analysed by modified intention-to-treat. Efficacy was investigated with linear mixed-effects models. Cost-effectiveness was investigated from a societal perspective by comparing costs with quality-adjusted life-years (QALYs). RESULTS: Participants who received bCBT reported significantly lower FCR compared with CAU (mean difference of − 1.787 [95% CI -3.251 to − 0.323, p = 0.017] at 15 months follow-up), and proportionally greater self-rated and clinically significant improvement at each follow-up measurement. Total QALYs were non-significantly different between conditions when adjusted for utility score baseline differences (0.984 compared to 0.957, p = 0.385), while total costs were €631 lower (95% CI -1737 to 2794, p = 0.587). Intervention costs of bCBT were €466. The incremental cost-effectiveness ratio amounted to an additional €2049 per QALY gained, with a 62% probability that bCBT is cost-effective at a willingness to pay (WTP) threshold of €20,000 per QALY. Results were confirmed in sensitivity analyses. CONCLUSIONS: bCBT for cancer survivors with FCR is clinically and statistically more effective than CAU on the long-term. In addition, bCBT is a relatively inexpensive intervention with similar costs and QALYs as CAU. TRIAL REGISTRATION: The RCT was registered in the Dutch National Trial Register (NTR4423) on 12-Feb-2014. This abstract was previously presented at the International Psycho-Oncology Society conference of 2018 and published online. (Psycho-oncology, 27(S3):8-55; 2018) ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-019-5615-3) contains supplementary material, which is available to authorized users.